2003
DOI: 10.1002/cncr.11827
|View full text |Cite
|
Sign up to set email alerts
|

Risk and timing of hospitalization for febrile neutropenia in patients receiving CHOP, CHOP‐R, or CNOP chemotherapy for intermediate‐grade non‐Hodgkin lymphoma

Abstract: BACKGROUNDHospitalization for chemotherapy‐induced febrile neutropenia is associated with substantial cost and may negatively impact clinical outcome due to associated dose attenuation.METHODSMedical records of 1355 patients with intermediate‐grade non‐Hodgkin lymphoma receiving cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) or similar chemotherapy were reviewed. The potential risk factors associated with first hospitalization for febrile neutropenia were evaluated.RESULTSIn the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
4
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 15 publications
(18 reference statements)
10
118
4
3
Order By: Relevance
“…In agreement with a report by Mayordomo et al (17), 53.7% of all FN events (22/41) occurred during cycle 1. Lyman et al (18) reported that a lack of primary prophylaxis with G-CSF in cycle 1 was associated with an increased risk of FN (18). However, although primary prophylaxis of G-CSF for almost all patients was administered in the present study, the FN occurrence rate in cycle 1 was the highest of all the treatment cycles.…”
Section: Resultscontrasting
confidence: 50%
“…In agreement with a report by Mayordomo et al (17), 53.7% of all FN events (22/41) occurred during cycle 1. Lyman et al (18) reported that a lack of primary prophylaxis with G-CSF in cycle 1 was associated with an increased risk of FN (18). However, although primary prophylaxis of G-CSF for almost all patients was administered in the present study, the FN occurrence rate in cycle 1 was the highest of all the treatment cycles.…”
Section: Resultscontrasting
confidence: 50%
“…14 Similar findings have been reported from a retrospective analysis of patients with non-Hodgkin lymphoma in which the receipt of Ն 80% of the intended dose was associated significantly with an increase in complete response rates. 39 Furthermore, hospitalization for febrile neutropenia during the first cycle of chemotherapy, when NH often occurs, 8 has been associated with an increased risk of early termination of the chemotherapy, 10 thus preventing patients from receiving the benefit of a full course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of developing neutropenia varies for each individual regimen; currently, predictions are based on the treatment regimen used and the experience of the attending physician (Sato et al, 2012 anticancer drugs (Lyman and Delgado, 2003;Millward et al, 2003;Timmer-Bonte et al, 2005). By contrast, few investigations have examined the predictive factors for neutropenia after docetaxel-based systemic chemotherapy in patients with CRPC.…”
Section: Predictive Factors For Neutropenia After Docetaxel-based Sysmentioning
confidence: 99%